CROSS-LAGGED STUDY OF EXPECTATION MISMATCHES AND PROACTIVE WORK ADAPTATION RESPONSES - Pinazo Calatayud, Daniel; Gracia Lerín, Francisco; Carrero Planes, Virginia (Anales de Psicología / Annals of Psychology, 2000)
This paper analyse the differences in the evolution of expectation mismatches linking with work proactive responses in new European employees Together are interviews over one and a half year period with two measurements. One group of employees (N=853) remained in the same organization at both points of measurement, whilst another group (N=257) had moved on to another organization at the second point of measurement.. The results show the breaking socilization process after de organizational change. In the other same the results suggest the interactive participation of expectation mismatches and adaptation proactive responses in the organizational socialization process. The conclusions enhance the debate in relation to the importance to the expectation mismatches in the organizational socialization process in the positive sense.